2006
DOI: 10.1016/j.otohns.2006.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Taste Disturbance after Uvulopalatopharyngoplasty for Obstructive Sleep Apnea

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…There have been several reports on gustatory dysfunction following otolaryngological surgery (e.g., palatal surgery, tonsillectomy, microlaryngoscopy, and otologic surgery) . To the best of our knowledge, there has been only one study that reported the change of gustatory function in tongue base surgery for OSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports on gustatory dysfunction following otolaryngological surgery (e.g., palatal surgery, tonsillectomy, microlaryngoscopy, and otologic surgery) . To the best of our knowledge, there has been only one study that reported the change of gustatory function in tongue base surgery for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…There is no gold standard test for gustatory function. Among various gustatory function tests (the three‐drop method, taste strips, electrogustometry, and spatial taste test), the three‐drop method using four main flavors (sweet, salty, sour, and bitter) has been widely used to examine basic tastes due to its clinical convenience and good test–retest reliability . In this study, we applied the three‐drop method to examine the taste changes at week 1, month 1, and month 3 after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out the difference in EGM scores, statistical analysis was performed approaches such as uvulopalatopharyngoplasty (UPPP) 6) and radiofrequency tongue base reduction 7) to treat SDB.…”
Section: Discussionmentioning
confidence: 99%
“…10 There are reports on gustatory dysfunction following surgery (eg, palatal surgery, tonsillectomy, microlaryngoscopy, and otologic surgery). [10][11][12][13][14][15] The causes of gustatory dysfunction after oropharyngeal surgery for OSA may include damage to the lingual branch of the glossopharyngeal nerve, excessive excision of taste receptors on the soft palate, mechanical pressure to the tongue, or lack of dietary zinc. 14 Gustatory dysfunction as a complication following surgery for OSA has been rarely reported in the literature.…”
mentioning
confidence: 99%